Antioxidants in Foods and Its Applications 2018
DOI: 10.5772/intechopen.74772
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of the Doum Palm (Hyphaene thebaica L.) Extract and Its Bioactive Components

Abstract: The doum palm (Hyphaene thebaica) is a type palm tree which has a wood texture and has edible oval fruits and the origin native to upper Egypt. The trunk of this small palm is dichotomous. It is one of the most important useful plants in the world. All parts of doum palm have a useful role such as fiber and leaflets which used to weave baskets and doum nuts which have antioxidants and secondary metabolites such as tannins, phenols, saponin, steroids, glycosides, flavonoid, terpenes and terpinoids. Also, roots,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 45 publications
0
26
1
Order By: Relevance
“…Although there is no available data on the impact of doum palm on fish growth and feed intake, the growth improvement offered by dietary doum palm can be returned to better nutritional status. High contents of proteins (2.86-5.01%), fibers (52.26-66.5%), essential fatty acids, vitamins, and minerals in doum palm justify its high nutritional value [21,23]. Moreover, the mesocarp of doum palm is very palatable and highly aromatic with a sweet smell [55].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there is no available data on the impact of doum palm on fish growth and feed intake, the growth improvement offered by dietary doum palm can be returned to better nutritional status. High contents of proteins (2.86-5.01%), fibers (52.26-66.5%), essential fatty acids, vitamins, and minerals in doum palm justify its high nutritional value [21,23]. Moreover, the mesocarp of doum palm is very palatable and highly aromatic with a sweet smell [55].…”
Section: Discussionmentioning
confidence: 99%
“…Pectins present in DPFP may lower the total cholesterol by reducing the cholesterol absorption from the diet and, therefore, may be attributed to the cholesterol and triglyceride-lowering effect of DPFP [74]. The lipid-lowering effect of DPFP can also be explained by its high content of antioxidants, such as flavonoids and polyphenols compounds, that prevent lipid peroxidation and formation of lipo-peroxides, which are atherosclerosis agents [21,75]. Moreover, glycosides (saponins) present in doum palm are known to form complexes with cholesterol and bile in the intestine, thereby indirectly reducing the cholesterol level in the blood, which may also rationalize this effect of DPFP [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, studies showed that Doum fruit has good nutritional and pharmaceutical properties; it contains carbohydrates, fibers, essential minerals, vitamin B-complex substantial for good nutrition, in addition to good amounts of phenolic compounds which are important in regulating various physiological processes in the human body [8,9]. Studies on Doum fruits have revealed a wealth of curative agents; it was found that Doum fruit is a good source of potent antioxidants and anticancer compounds [10,11], anti-inflammatory, anti-proliferative and antimicrobial activity [12].…”
Section: Introductionmentioning
confidence: 99%